2024
DOI: 10.1021/acs.jafc.3c06083
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis Reveals Candidate Pathways Related to the Effect of Different Light Qualities on the Development of Mycelium and Fruiting Body of Pleurotus ostreatus

Liping Zhu,
Yao Su,
Shunan Ma
et al.

Abstract: Light affects the morphology and physiology of Pleurotus ostreatus. However, the underlying molecular mechanism of this effect remains unclear. In this study, a label-free comparative proteomic analysis was conducted to investigate the global protein expression profile of the mycelia and fruiting bodies of P. ostreatus PH11 growing under four different light quality treatments. Among all the 2234 P. ostreatus proteins, 1349 were quantifiable under all tested conditions. A total of 1100 differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…A recent study of P. ostreatus mycelia and basidioma proteomic analysis under different light wavelengths revealed that basidioma and mycelia present different responses under light, with white and blue light significantly promoting basidioma growth while red light and darkness significantly inhibited this growth. Concerning mycelia production in Petri dishes, the same study indicates that mycelia production is favored under white light while red light and darkness present morphological differentiation [40]. A study of the strain Phanerochaete chrysosporium summarizes that biomass production is favored under conditions of yellow and green light [41].…”
Section: Discussionmentioning
confidence: 92%
“…A recent study of P. ostreatus mycelia and basidioma proteomic analysis under different light wavelengths revealed that basidioma and mycelia present different responses under light, with white and blue light significantly promoting basidioma growth while red light and darkness significantly inhibited this growth. Concerning mycelia production in Petri dishes, the same study indicates that mycelia production is favored under white light while red light and darkness present morphological differentiation [40]. A study of the strain Phanerochaete chrysosporium summarizes that biomass production is favored under conditions of yellow and green light [41].…”
Section: Discussionmentioning
confidence: 92%